Impatiens damingensis (Balsaminaceae), a new species from Guangxi, China - Xia, Chang-Ying; Gadagkar, Sudhindra R.; Li, Jin; Deng, Hong-Ping; Yu, Sheng-Xiang (Phytotaxa, 2019)
Impatiens damingensis S. X. Yu, C. Y. Xia & H. P. Deng, (Balsaminaceae) discovered in Guangxi, China, is described and illustrated here. This species is similar to I. aquatilis Hook.f., but differs from the latter by having blades that are ovate or ovate-lanceolate vs. lanceolate, ovate-lanceolate, or ovate-oblong; apices of bracts acute vs. glandular awned; apices of lateral sepals mucronulate vs. long mucronulate; and spur slender substraight or slightly incurved vs. incurved. Furthermore, molecular data as well as micro-morphological evidence under SEM (of pollens and seeds) also support the establishment of the new species.